Increase serum leptin level in Helicobacter pylori infection in Iraqi gastritis patients - ’a Khudhur, Sana; Jameel; Karhoot, Jasim; AL-Khafaji, Jasim; Mohsin, Jasim (AL-Kindy College Medical Journal, 2011)
Background: H.pylori colonized gastric mucosalepithelium will virtually develop gastritis and had thecapacity to persist for decades. Pathogenesis isdependent upon strain, virulence host geneticsusceptibility, and environmental cofactors. Leptin isa member of the class 1 cytokine family so alteredleptin production during ifnect and inflammation thatleptin part of the cytokine cascade ,whichorchestrates the defense mechanism.Objective: Examin the effect of H.pylori infectionon serum leptin level.Methods: One hundred and thirty(130) Patientsattending the Endoscopic Unit at "Gastroenterologyand Hepatology Teaching Hospital/ Baghdad MedicalCity"were included in this study with ages rangefrom 18 years to 65 years are the source of specimensto undergo oesophageal gastroduodenoscopy (OGD)compared with twenty healthy control the studybegan from April 2009 to the end of March 2010were eligible for this study.Tow types of sampleswere taken, biopsy for rapid urease test andhistopathological examination to detect H.pylori andblood sample for estimation of serum leptin byELISA test.Results: The results show significant increase inserum leptin concentration(P